Differential PCR diagnosis of bacterial vaginosis, aerobic vaginitis and vulvovaginal candidiasis - T. I. Makhova; T. A. Rumyantseva; E. N. Goloveshkina; V. G. Akimkin (Фундаментальная и клиническая медицина, 2022)
Aim. To evaluate the effectiveness of PCR tests to diagnose common pathological conditions associated with vaginal discharge (i.e. bacterial vaginosis, aerobic vaginitis, and vulvovaginal candidiasis) in patients with and without complaints.Materials and Methods. The study enrolled 240 women which flled out an original questionnaire on demographic, social, behavioral, and reproductive features and underwent a vaginal examination. Real-time PCR of vaginal smears was used to detect bacterial vaginosis, aerobic vaginitis, vulvovaginal candidiasis, and sexually transmitted infections (Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Mycoplasma genitalium).Results. Sexually transmitted infections have not been detected in women included into the study. Almost half (46%) of the patients had gynecological complaints; these patients also had higher prevalence of vaginal dysbiosis. PCR analysis determined vaginal dysbiosis in > 45% of women with complaints. In around 25% women without any complaints, microorganisms prevailed over lactobacteria that suggested vaginal dysbiosis. Among the behavioural factors, only douching was signifcantly associated with vaginal dysbiosis.Conclusion. PCR tests were able to defne vaginal dysbiosis in almost half of the patients and were effcient in patients both with or without complaints.